The Effect of Motivation and Career Development on Employee Performance with Job Satisfaction as Intervening Variable: The Case of Education and Culture Office of Banyuasin Regency - Miftakul Mu’minin; Trisniarty Adjeng Moelyati; Fadhil Yamaly (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study aims to determine 1) the Effect of Motivation on Employee Job Satisfaction at the Banyuasin Regency Education and Culture Office. 2) The Influence of Career Development on Job Satisfaction of Employees of the Education and Culture Office of Banyuasin Regency. 3) The Influence of Motivation on the Performance of Employees of the Education and Culture Office of Banyuasin Regency. 4) The Influence of Career Development on the Performance of Employees of the Education and Culture Office of Banyuasin Regency. 5) The Influence of Job Satisfaction on the Performance of Employees of the Education and Culture Office of Banyuasin Regency. This type of research is Associative. The population of this study consisted of all employees (179), and the sample comprised 120 employees; the sampling technique used was cluster sampling. The data used in this study are primary, collected through a questionnaire. The data analysis technique used is Structural Equation Modeling (SEM) with the LISREL program. The results of this study indicate that: 1) there is a significant influence of Motivation on Job Satisfaction. 2) There is a significant influence of Career Development on Job Satisfaction. 3) There is a significant influence of Motivation on Employee Performance. 4) Career Development has a significant influence on Employee Performance. 5) Job Satisfaction has a significant influence on Employee Performance. Job Satisfaction strengthens the influence of Motivation and Career Development on Employee Performance at the Banyuasin Regency Education and Culture Office